Preparation, Characterization And Properties Of Polypropylene/Waste Tyre Dust/Kenaf Powder Composites - Pang, Ai Ling (2013)
Thermoplastic elastomer composites of polypropylene (PP)/waste tyre dust (WTD)/kenaf powder (KNFp) were prepared with a fix thermoplastic elastomer blend composition of PP/WTD at 70/30 (wt./wt.%). The amount of KNFp used in this research was 0, 5, 10, 15 and 20 phr. All composites were prepared using a Thermo Haake Rheomix Polydrive R600/610 internal mixer at temperature of 180°C and rotor speed of 50 rpm for a mixing time of 10 minutes. The results showed that the stabilization torque, tensile modulus, water uptake and thermal stability of composites increased with increasing KNFp loading. However, the tensile strength and elongation at break was decreased. By substituting KNFp with kenaf short fiber (KNFs), the tensile strength and tensile modulus of the composites were higher. However, the increasing in processing torque causes a difficulty during preparation of the PP/WTD/KNFs composites. Addition of 3-aminopropyltriethoxysilane (APTES) to the composites has resulted in higher stabilization torque, tensile strength and tensile modulus, whereas the elongation at break and water uptake were lower. APTES was found to be effective to act as coupling agent due to the enhancement in interfacial adhesion of the composites, as shown by the SEM micrographs. For PP/WTD/KNFp composites with the addition of phthalic anhydride (PA), tensile strength, tensile modulus and water uptake were increased, but the elongation at break and processing torque were decreased.